Differences of skin carotenoids and adherence to the Mediterranean Diet pattern in adults from Southern Italy and Dominican Republic - Giuseppina Augimeri; Manuel Soto; Fabrizio Ceraudo; Giovanna Caparello; Melisa Villegas Figueroa; Mirko Cesario; Lorenzo S. Caputi; Berniza Calderón; Daniela Bonofiglio (Journal of Translational Medicine, 2024)
Abstract Background The measurement of the skin carotenoids using the Veggie Meter® has emerged as a rapid objective method for assessing fruit and vegetable intake, highly recommended by the Mediterranean Diet (MD), which represents one of the healthiest dietary patterns, worldwide. This study aimed to examine differences in skin carotenoid content and degree of adherence to the MD pattern between two adult populations from Southern Italy and the Dominican Republic. Methods This cross-sectional study enrolled a total of 995 adults, 601 subjects from Italy and 394 from the Dominican Republic. All participants underwent anthropometric measurements and skin carotenoid assessment by Veggie Meter®. Adherence to the MD and lifestyle were evaluated using the Mediterranean Diet Adherence Screener (MEDAS) and the Mediterranean Lifestyle Index (MEDLIFE) questionnaires. Correlations between the skin carotenoid and MEDAS score were estimated using Pearson’s correlation coefficient. Multiple linear regression models were created to determine variables that affect skin carotenoid score for both populations. Results Mean total skin carotenoids were higher in the Italian compared to the Dominican Republic population (342.4 ± 92.4 vs 282.9 ± 90.3; p < 0.005) regardless of sex (women: 318.5 ± 88.9 vs 277.3 ± 91.9, p < 0.005 and men: 371.7 ± 88.3 vs 289.5 ± 88.1, p < 0.005), and remaining statistically significant after age-adjustment of the Dominican Republic sample. Using the MEDAS questionnaire, we found a higher MD adherence score in the Italian than in the Dominican Republic population also after age-adjusting data (7.8 ± 2.1 vs 6.2 ± 3.7; p < 0.005) and even when categorized by sex (Italian vs age-adjusted Dominican Republic women: 7.9 ± 2.1 vs 6.3 ± 2.6; Italian vs age-adjusted Dominican Republic men: 7.7 ± 2.2 vs 6.0 ± 4.7; p < 0.005). Using the MEDLIFE test, total Italians presented a lower score with respect to the age-adjusted Dominican Republic population (3.2 ± 1.2 vs 3.4 ± 1.4; p < 0.05). In multiple regression analysis, skin carotenoids were associated with sex and negatively associated with BMI in the Italian population (sex: β: 54.95; 95% CI: 40.11, 69.78; p < 0.0001; BMI: β: − 1.60; 95% CI: − 2.98,0.86; p = 0.03), while they resulted associated with age and sex in the Dominican Republic population (age: β: 2.76; 95% CI: 1.92, 3.56; p < 0.001; sex: β: 23.29; 95% CI: 5.93, 40.64; p = 0.009). Interestingly, skin carotenoids were positively correlated with MEDAS score in both populations (Italy: r = 0.03, p < 0.0001, Dominican Republic: r = 0.16, p = 0.002). Conclusions This study provides the assessment of the adherence to the MD and skin carotenoid content in adults living in Southern Italy and the Dominican Republic, showing a higher MD adherence score and a skin carotenoid content in inhabitants from the Mediterranean region. Our findings highlight the need to globally encourage fruit and vegetable intake, particularly in non-Mediterranean area.